Product Quality Analysis Safety Belt to Reduce Disability Using Six Sigma Method and Repair with Kaizen in PT XYZ - Alamsyah, Ivan; Rochmoeljati, Rr. (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT XYZ is a company engaged in the automotive spare parts sector. In carrying out production activities, there is a problem, namely defects in the safety belt product because of rust defects. From September 2022 to February 2023, the company produced safety belts amounting to 32,611 units and there are product defects rust of 1,709 units or around 5.24% of the total production. The product defect This will cause losses to the company and can reduce consumer confidence in the products produced by the company. Given this problem, research was carried out using the Six Sigma method and improvements to Kaizen the Five M Checklist also the Kaizen Five-Step Plan. The research aim is to reduce defects and make improvements to achieve near-perfect results. From September 2022 to February 2023, there is a DPMO of 51,856 and is at a sigma level of 3.1616. To reduce defects in safety belt production, the proposed improvements are based on the implementation of kaizen to improve product quality, namely getting used to working according to Standard Operating Procedures (SOP), applying strict sanctions when making mistakes repeatedly, carrying out periodic machine maintenance, facilitating air circulation by making air vents and others.